2015
DOI: 10.1093/aobpla/plw013
|View full text |Cite
|
Sign up to set email alerts
|

How to make a red flower: the combinatorial effect of pigments

Abstract: This study examines the biochemical basis of red flowers in the tomato family, Solanaceae. We show that red-flowered species have converged on the same floral hue using either the sole production of red anthocyanin pigments or, more commonly, the dual production of purple or blue anthocyanins and orange carotenoid pigments. The use of blue anthocyanins in red flowers appears to differ from other groups, and suggests that the genetic changes underlying evolutionary transitions to red flowers may not be as predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 91 publications
1
30
0
Order By: Relevance
“…2b). This chemical prole would likely result in red or pink oral coloration (Ng and Smith 2016a;Smith and Rausher 2011).…”
Section: Resultsmentioning
confidence: 99%
“…2b). This chemical prole would likely result in red or pink oral coloration (Ng and Smith 2016a;Smith and Rausher 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, comparative studies have shown that red‐coloured flowers can result from various combinations of pigments (e.g. purple anthocyanins plus orange carotenoids; Ng & Smith, ,b), providing multiple pathways for evolutionary transitions among colours.…”
Section: Discussionmentioning
confidence: 99%
“…These independent origins of red flowers have involved at least three different developmental mechanisms and two distinct pigment pathways (Ng & Smith, 2016a). Specifically, red flower coloration can be due to the presence of anthocyanin pigments, carotenoid pigments or the production of both (Ng & Smith, 2016b). The potential for producing red flowers via multiple types of genetic and biochemical changes may help to explain the evolutionary lability of this trait, with many gains and losses (Perret et al, 2003;Tripp & Manos, 2008), as well as the widespread convergence on this colour across angiosperms (Cronk & Ojeda, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…(). Given that flower color is preserved in herbarium specimens, we also sampled flowers from several collections () as in Ng and Smith (). In addition, we conducted a comprehensive literature search to collect previously published data on floral anthocyanin composition in Solanaceae ().…”
Section: Methodsmentioning
confidence: 99%
“…). Among the three types, those derived from delphinidin appear to be the most commonly produced in floral tissue, followed by cyanidin and pelargonidin (Ng and Smith ). The wide phylogenetic distribution of taxa with similar pigment profiles suggests that shifts in anthocyanin production have occurred multiple times in the family, providing the foundation for modeling evolutionary transitions.…”
mentioning
confidence: 99%